Renal Impairment, Recurrent Venous Thromboembolism and Bleeding in Cancer Patients with Acute Venous Thromboembolism—Analysis of the CATCH Study - Bauersachs, Rupert; Lee, Agnes Y. Y.; Kamphuisen, Pieter W.; Meyer, Guy; Janas, Mette S.; Jarner, Mikala F.; Khorana, Alok A.; on behalf of the CATCH Investigators (Thrombosis and Haemostasis, 2018)
Objective This article assesses the impact of renal impairment (RI) on the efficacy and safety of anticoagulation in patients with cancer-associated thrombosis from the Comparison of Acute Treatments in Cancer Hemostasis (CATCH) study (NCT01130025).Materials and Methods Renal function was assessed using the Modification of Diet in Renal Disease equation in patients with cancer-associated thrombosis who received either tinzaparin (175 IU/kg) once daily or warfarin for 6 months, in an open-label, randomized, multi-centre trial with blinded adjudication of outcomes. Associations between baseline RI (glomerular filtration rate [GFR] <60 mL/min/1.73m2) and recurrent symptomatic or incidental venous thromboembolism (VTE), clinically relevant bleeding (CRB), major bleeding and death were assessed using Fisher's exact test.Results Baseline-centralized GFR data were available for 864 patients (96% of study population). RI was found in 131 patients (15%; n = 69 tinzaparin). Recurrent VTE occurred in 14% of patients with and 8% of patients without RI (relative risk [RR] 1.74; 95% confidence interval [CI] 1.06, 2.85), CRB in 19% and 14%, respectively (RR 1.33; 95% CI 0.90, 1.98), major bleeding in 6.1% and 2.0%, respectively (RR 2.98; 95% CI 1.29, 6.90) and mortality rate was 40% and 34%, respectively (RR 1.20; 95% CI 0.94, 1.53). Patients with RI on tinzaparin showed no difference in recurrent VTE, CRB, major bleeding or mortality rates versus those on warfarin.Conclusion RI in patients with cancer-associated thrombosis on anticoagulation was associated with a statistically significant increase in recurrent VTE and major bleeding, but no significant increase in CRB or mortality. No differences were observed between long-term tinzaparin therapy and warfarin.
Keywords: cancer-associated thrombosis; recurrent venous thromboembolism; renal impairment; anticoagulation; tinzaparin